MENOPAUSAL SYMPTOMS AND FISH CONSUMPTION OF MENOPAUSAL WOMEN IN THE COASTAL AREAS OF SOUTHEAST SULAWESI, INDONESIA - Saimin, Juminten; Ridwan, Steven; Yohanis, Mono Valentino; Lianawati, Lianawati; Arimaswati, Arimaswati; Hamliati, Hamliati (Public Health of Indonesia, 2020)
Background: Menopausal symptoms are common problem in menopausal women. The severity of menopausal symptoms is influenced by the interaction of biological, genetic and nutritional factors.Objective: This study aimed to determine correlation between menopausal symptoms and fish consumption of postmenopausal women in the coastal areas.Method: This was a cross-sectional study conducted on 234 postmenopausal women in the coastal areas of Southeast Sulawesi. Severity of menopausal symptoms was assessed using Menopause Rating Scale (MRS). Quantity of fish consumption was calculated using 24-hour recall questionnaires. Frequency of fish consumption was evaluated using Food Frequency Questionnaires (FFQ). Data analysis used Chi-square test with a significance value of p=0.05.Results: The majority of fish consumption was sufficient in quantity (81.6%) and frequency (95.3%). Menopausal symptoms are found to be very mild (14.1%), mild (36.3%), moderate (38.5%), and severe (11.1%). There was a correlation between menopausal symptoms and the quantity of fish consumption (p=0.000), and between menopausal symptoms and the frequency of fish consumption (p=0.000).  Conclusion: There was a correlation between menopausal symptoms and fish consumption of postmenopausal women, both in the quantity and frequency. Therefore, increasing the quantity and frequency of fish consumption will reduce the severity of menopausal symptoms.